Communicating the museum between analogue and digital. Interactive multimedia design experience - Federica Dal Falco; Silvia Bonomi (Agathón)
This paper deals with the relationship between museum communication and information technologies, providing an overview of the main international references that witness the evolution of museums between analogue and digital, up to the radicality of immersive environments. The theoretical apparatus is integrated by the proposal of a methodology between multimedia and IoT, experimented in order to create synergies between research and third mission, implemented through the interdisciplinary project Interactive Multimedia Museum Experience, a model of museum communication that in its variants has been validated in recent years in prestigious museum institutions in the city of Rome.